Asymptotic Behavior of Solutions to a Linear Volterra Integrodifferential System - Yue-Wen Cheng; Hui-Sheng Ding (Abstract and Applied Analysis)
We investigate the asymptotic behavior of solutions to a linear Volterra integrodifferential system , We show that under some suitable conditions, there exists a solution for the above integrodifferential system, which is asymptotically equivalent to some given functions. Two examples are given to illustrate our theorem.